The Effectiveness of Court Decisions in Imposing Sentences on Corruptors in Indonesia: Justice and Deterrence Analysis (Discourse Journal on Law and Society, 2025)
Corruption continues to be one of Indonesia’s most severe criminal issues, generating substantial financial losses for the state and obstructing the country’s development efforts. Judicial rulings in corruption cases therefore play a vital role in supporting anti-corruption initiatives, both in terms of ensuring fairness and creating a strong deterrent effect. This study evaluates how effective court decisions are in sentencing corruptors in Indonesia by analyzing justice and deterrence dimensions through a socio-legal research approach supported by descriptive analysis. The findings indicate that the effectiveness of judicial decisions remains limited due to disparities in sentencing, lenient punishments that fail to reflect a sense of justice, and the influence of various legal as well as extralegal factors. These issues weaken the credibility of the judicial process and reduce the intended preventive impact of court-imposed sanctions. To enhance effectiveness, the study highlights the need for comprehensive reforms, including clearer sentencing guidelines, improved law enforcement capabilities, and stronger oversight mechanisms to ensure accountability. Overall, this research enhances understanding of the structural challenges within Indonesia’s anti-corruption justice system and proposes recommendations aimed at reinforcing the deterrent value of court decisions through sentencing practices that are more consistent, proportionate, and aligned with the severity of corruption offenses.